Contrasting Health Literacy in Physical Activities: A Study Across Various Academic Stages in Exercise and Sport Science Students - Julavanichpong, Tanida; Hanmanop, Kittipob; Huan-Kim, Thanakorn; Maneejak, Thiranat; Namthongton, Napas; Suwatthanapiriy, Veerapat; Sucharit, Satanachan; Singhnoi, Chatkamon; Choosakul, Chairat (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2023)
This research aimed to assess health literacy regarding physical activities among Exercise and Sports Science students across different academic years. Involving 194 students selected via simple random sampling from Burapha University, the study utilised a comprehensive questionnaire A pivotal instrument in this methodology was the